26+3x=-13

Simple and best practice solution for 26+3x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26+3x=-13 equation:



26+3x=-13
We move all terms to the left:
26+3x-(-13)=0
We add all the numbers together, and all the variables
3x+39=0
We move all terms containing x to the left, all other terms to the right
3x=-39
x=-39/3
x=-13

See similar equations:

| 2/3r+15=17 | | -20=3x-7+x | | -4+k/4=-6 | | 12-6k=2(6-3k) | | q/(-2)=8 | | 0.4r−1.2=0.3r+0.6 | | 2/5n+1/10=1/2n+3 | | 14x2x+12=12x2x+5 | | 1.4=28/x | | 22=-8u+6(u+4) | | 7w=-11 | | 19+x=17-5x | | 2p-8/p+3=8/10 | | -279=-9x | | 8.16-0.2n=-13.8n | | 2(1/2x+6)=3(x+-3) | | 21=-3x+15 | | -8-4x=-2x+22 | | 8z-4(z+8)=8 | | 4y−6=y−6 | | y=1000(1.4^4) | | 1q+2=6 | | (w)/(-2.5)=8 | | 1/24=-8/9k | | 48=-5s | | 15-5g=50 | | -5a+5=a+5 | | 3x+8x-16=8x+1 | | -3(3x-4)=-9x+12 | | 6/7x(5/4/7)(=7/8 | | 8+4a=8a | | x=15/21=26/7 |

Equations solver categories